Polymerase synthesis of oligonucleotides containing a single chemically modified nucleobase for site-specific redox labelling - Ménová, Petra; Cahová, Hana; Plucnara, Medard; Havran, Luděk; Fojta, Miroslav; Hocek, Michal (Chemical communications (Cambridge, England), 2013)
Enzymatic construction of single-nucleobase redox-labelled oligonucleotides was developed either based on polymerase incorporation of a single modified nucleoside triphosphate (dNTP) followed by primer extension (PEX) with natural dNTPs or based on PEX with a biotinylated one-nucleotide overhang template, magnetoseparation and the second PEX with a full-length template.
Keywords: DNA-Directed DNA Polymerase; DNA Primers; guanosintrifosfát; metaloceny; nitrobenzeny; oxidace-redukce; železnaté sloučeniny; DNA-dependentní DNA-polymerasy; Ferrous Compounds; Guanosine Triphosphate; Nucleotides; Oligonucleotides; Metallocenes; oligonukleotidy; Nitrobenzenes; Oxidation-Reduction; DNA primery; nukleotidy